The Effectiveness of Family-Based Health Education Programs on Managing Type 2 Diabetes - Albahrani , Suha (South Eastern European Journal of Public Health, 2024)
Background: Type 2 Diabetes Mellitus (T2DM) is a global public health challenge that requires comprehensive management strategies. Family-based health education programs have emerged as a promising approach to enhance glycemic control, self-care behaviors, and patient outcomes by leveraging the supportive role of family members. Objective: To evaluate the effectiveness of a family-based health education program on the management of T2DM in Al-Hofuf City, Saudi Arabia. Methods: A quasi-experimental study was conducted involving 140 participants (70 patients with T2DM and 70 family members) recruited from three primary healthcare centers. Participants underwent a 12-week culturally tailored educational program focused on diabetes management, self-care practices, and family support. Pre- and post-intervention assessments included glycated hemoglobin (HbA1c), fasting blood glucose, body mass index (BMI), diabetes knowledge, self-care behaviors, and family support using validated tools. Results: Significant improvements were observed post-intervention in HbA1c levels (mean reduction: 0.7%; p < 0.001), fasting blood glucose (mean reduction: 18.4 mg/dL; p < 0.001), and BMI (mean reduction: 0.9 kg/m²; p = 0.02). Diabetes knowledge, self-care behaviors, and family support scores increased significantly (p < 0.001). Correlation analysis revealed strong associations between family support and improved glycemic control and self-care practices. Conclusion: Family-based health education programs significantly improve glycemic control, self-care behaviors, and family support among patients with T2DM. These findings highlight the importance of incorporating family-centered approaches into diabetes management to address cultural and social dynamics effectively.